Endothelial Cell Response to Chemical, Biological, and Physical Cues in Bioactive Hydrogels - Browning, Mary Beth (Tissue Eng Part A, 2014)
The highly tunable biological, chemical, and physical properties of bioactive hydrogels enable their use in an array of tissue engineering and drug delivery applications. Systematic modulation of these properties can be used to elucidate key cell–material interactions to improve therapeutic effects. For example, the rate and extent of endothelialization are critical to the long-term success of many blood-contacting devices. To this end, we have developed a bioactive hydrogel that could be used as coating on cardiovascular devices to enhance endothelial cell (EC) adhesion and migration. The current work investigates the relative impact of hydrogel variables on key endothelialization processes. The bioactive hydrogel is based on poly(ethylene glycol) (PEG) and a streptococcal collagen-like (Scl2-2) protein that has been modified with integrin α(1)β(1) and α(2)β(1) binding sites. The use of PEG hydrogels allows for incorporation of specific bioactive cues and independent manipulation of scaffold properties. The selective integrin binding of Scl2-2 was compared to more traditional collagen-modified PEG hydrogels to determine the effect of integrin binding on cell behavior. Protein functionalization density, protein concentration, and substrate modulus were independently tuned with both Scl2-2 and collagen to determine the effect of each variable on EC adhesion, spreading, and migration. The findings here demonstrate that increasing substrate modulus, decreasing functionalization density, and increasing protein concentration can be utilized to increase EC adhesion and migration. Additionally, PEG-Scl2-2 hydrogels had higher migration speeds and proliferation over 1 week compared with PEG-collagen gels, demonstrating that selective integrin binding can be used to enhance cell–material interactions. Overall, these studies contribute to the understanding of the effects of matrix cues on EC interactions and demonstrate the strong potential of PEG-Scl2-2 hydrogels to promote endothelialization of blood-contacting devices.